Cost Evaluation of 3D Concrete Printing in the UAE Construction Industry - Alhomsi, Mhd Amjad (2023)
A Master of Science thesis in Construction Management by Mhd Amjad Alhomsi entitled, “Cost Evaluation of 3D Concrete Printing in the UAE Construction Industry”, submitted in November 2023. Thesis advisor is Dr. Adil Kahwash Al-Tamimi and thesis co-advisor id Dr. Ghanim Kashwani. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).